Schreibfokussierte Graduiertenförderung: Reflexive Spezialisierung für interdisziplinäre Forschungskontexte - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre)

Adding Why to What? Analyses of an Everyday Explanation - Terfloth, Lutz; Schaffer, Michael; Buhl, Heike M.; Schulte, Carsten
In XAI it is important to consider that, in contrast to explanations for professional audiences, one cannot assume common expertise when explaining for laypeople. But such explanations between humans vary greatly, making it difficult to research commonalities across explanations. We used the dual nature theory, a techno-philosophical approach, to cope with these challenges. According to it, one can explain, for example, an XAI's decision by addressing its dual nature: by focusing on the Architecture (e.g., the logic of its algorithms) or the Relevance (e.g., the severity of a decision, the implications of a recommendation). We investigated 20 game explanations using the theory as an analytical framework. We elaborate how we used the theory to quickly structure and compare explanations of technological artifacts. We supplemented results from analyzing the explanation contents with results from a video recall to explore how explainers justified their explanation. We found that explainers were focusing on the physical aspects of the game first (Architecture) and only later on aspects of the Relevance. Reasoning in the video recalls indicated that EX regarded the focus on the Architecture as important for structuring the explanation initially by explaining the basic components before focusing on more complex, intangible aspects. Shifting between addressing the two sides was justified by explanation goals, emerging misunderstandings, and the knowledge needs of the explainee. We discovered several commonalities that inspire future research questions which, if further generalizable, provide first ideas for the construction of synthetic explanations.

What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022).

Alles anders und doch gleich?! - Auswirkungen der Digitalisierung und Folgen der Covid-19-Pandemie auf die unterrichtsbezogene Lehrerkooperation - Engemann, Mario; Herzig, Bardo

"Wir machen dann das, worauf wir Bock haben" - Eine empirische Analyse zur Bedeutung fachdidaktischer Überzeugungen für die unterrichtsbezogene Lehrerkooperation - Engemann, Mario

Schreiben als Wissensproduktion? Eine Mikroanalyse der Vielstimmigkeit akademischer Selbstbildung und Enkulturation - Karsten, Andrea (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Wie hängen Schreiben und Identität zusammen? Schreibberatung als Raum für die Thematisierung und Entwicklung eines 'Dialogical Self' - Karsten, Andrea (Neue Perspektiven auf Schreibberatung)

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

The effectiveness of vaccination, testing, and lockdown strategies against COVID-19 - Fritz, Marlon; Gries, Thomas; Redlin, Margarete (International Journal of Health Economics and Management)
Abstract The ability of various policy activities to reduce the reproduction rate of the COVID-19 disease is widely discussed. Using a stringency index that comprises a variety of lockdown levels, such as school and workplace closures, we analyze the effectiveness of government restrictions. At the same time, we investigate the capacity of a range of lockdown measures to lower the reproduction rate by considering vaccination rates and testing strategies. By including all three components in an SIR (Susceptible, Infected, Recovery) model, we show that a general and comprehensive test strategy is instrumental in reducing the spread of COVID-19. The empirical study demonstrates that testing and isolation represent a highly effective and preferable approach towards overcoming the pandemic, in particular until vaccination rates have risen to the point of herd immunity.
Keywords: Health Policy; Economics; Econometrics and Finance (miscellaneous)

Émile Durkheim: Father of the Sociology of Education - Lin-Januszewski, Liang-Wen (The Palgrave Handbook of Educational Thinkers)

Bolzano, Bernard: Briefe an Michael Josef Fesl 1837–1840. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1512.01036)

Wolfram, Stephen. Dropping in on Gottfried Leibniz. In: Unravelling Complexity: The Life and Work of Gregory Chaitin, hg. v. Francisco Antonio Doria und Shyam Wuppuluri, World Scientific: Hackensack, NJ 2020, 49–81 - Peckhaus, Volker (Mathematical Reviews MR4450759)

Bolzano, Bernard. Briefe an Michael Josef Fesl 1841–1845. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.4). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete ZBl 1512.01037)

Wolfgang Tschirk: Vom Universum des Denkens. Eine Geistesgeschichte der Logik. Springer: Berlin 2022 - Peckhaus, Volker (Mathematische Semesterberichte)

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Die schriftbildliche Gestaltung von lexikalisch übernommenen Markennamen. Ein explorativer Wahrnehmungstest zum graduellen Entrenchment von Markennamen als multimodale Konstruktionen - Dübbert, Alexander (Beiträge zur Namenforschung)
Dieser Beitrag untersucht, inwiefern sich die kognitive Verankerung von der schriftbildlichen Gestaltung lexikalisch übernommener Markennamen nachweisen lässt. Dazu werden die Ergebnisse eines tachistoskopischen Wahrnehmungstests ausgewertet, bei dem einer Testgruppe die Schriftbilder (Logos) der Markennamen 'FÜR', 'Landliebe', 'MONSTER', 'GUT & GÜNSTIG', 'kinder' und 'ja!' mehrmals für Sekundenbruchteile (0,01s, 0,02s, 0,1s und 1,0s) und teils mit substituiertem Schriftzug präsentiert wurden. Insgesamt deutet die explorative Untersuchung – mit graduellen Abweichungen – in die Richtung, dass die Wahrnehmung des Schriftbilds zum Erkennen des dazugehörigen Markennamens führt. Dies ermöglicht die Schlussfolgerung, dass sich die getesteten Markennamen als multimodale Konstruktionen mit konstitutiver Schriftbildlichkeit qualifizieren.

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

Teacher's roles and teacher professionalism - Lin-Januszewski, Liang-Wen (Sociology of education: Theory, experience and implication)

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Die Rechtfertigung des Kapitalismus und die Kritik. Der neue Geist des Kapitalismus von Luc Boltanski und Ève Chiapello - Knoll, Lisa (Soziologische Gegenwartsdiagnosen 3)

Similar Affordances, Different Use Practices? An Investigation of Socio-Cultural Contexts in Facebook, Instagram and Twitter - Arslan, Kader; Trier, Matthias (Proceedings of the 44th International Conference on Information Systems (ICIS 2023))

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

Ernst Schröder’s Algebra of Logic and the ‘Logic of the Ancient - Peckhaus, Volker (Aristotle’s Syllogism and the Creation of Modern Logic: Between Tradition and Innovation, 1820s–1930s (Bloomsbury Studies in the Aristotelian Tradition))

Nakano, Anderson: On Ramsey’s Reason to Amend Principia Mathematica’s Logicism and Wittgenstein’s Reaction, Synthese 199 (2021), 2629–2646. - Peckhaus, Volker (Mathematical Reviews MR4341825)

Schappacher, Norbert. Framing Global Mathematics. The International Mathematical Union between Theorems and Politics, Springer: Cham 2022 - Peckhaus, Volker (Mathematical Reviews MR4461006)

Aranda, Victor. Completeness: From Husserl to Carnap. Logica Universalis 16 (2022), 57–83 - Peckhaus, Volker (Mathematical Reviews MR4451488)

Floyd, Juliet und Felix Mühlhölzer, Wittgenstein’s Annotations to Hardy’s Course of Pure Mathematics. An Investigation of Wittgenstein’s Non-Extensionalist Understanding of the Real Numbers, Springer: Cham 2020 (Nordic Wittgenstein Studies, 7). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07214204)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 6: Taschennotizbücher1931–32. Anmerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2022, xiii, 192 S. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07469681)

Hogan, Desmond, “Kant and the Character of Mathematical Inference”, in: Carl Posy et al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 126–154 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1570.01020)

Schlimm, Dirk, "Pasch’s Empiricism as Methodological Structuralism." In: Erich H. Reck und Georg Schiemer (eds.), The Prehistory of Mathematical Structuralism, Oxford: University Press 2020, 88–105 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.01017)

Bellomo, Anna und Guillaume Massas, Bolzano’s Mathematical Infinite. The Review of Symbolic Logic 16, No. 1 (2023), 59–113 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1515.01010)

Tschirk, Wolfgang, Vom Universum des Denkens. Eine Geistesgeschichte der Logik, Springer: Berlin 2022 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.03007)

Herrmann, Kay (Hg.), Grete Henry-Hermann: Philosophie – Mathematik – Quantenmechanik. Texte zur Naturphilosophie und Erkenntnistheorie, mathematisch-physikalische Beiträge sowie ausgewählte Korrespondenz aus den Jahren 1925 bis 1982. Springer VS: Wiesbaden 2019, xv + 664 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1506.01002)

SIG: Adaptivität und Adaptive Lehrkompetenz grundschulpädagogisch und (fach-)didaktisch reloaded - Reh, Anne; Schroeder, René; Miller, Susanne; Blumberg, Eva; Kottmann, Brigitte; Thevißen, Max

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (arXiv:2305.06632)
In this article we investigate the convergence behavior of gathering protocols with fixed circulant topologies using tools form dynamical systems. Given a fixed number of mobile entities moving in the Euclidean plane, we model a gathering protocol as a system of ordinary differential equations whose equilibria are exactly all possible gathering points. Then, we find necessary and sufficient conditions for the structure of the underlying interaction graph such that the protocol is stable and converging, i.e., gathering, in the distributive computing sense by using tools from dynamical systems. Moreover, these tools allow for a more fine grained analysis in terms of speed of convergence in the dynamical systems sense. In fact, we derive a decomposition of the state space into stable invariant subspaces with different convergence rates. In particular, this decomposition is identical for every (linear) circulant gathering protocol, whereas only the convergence rates depend on the weights in interaction graph itself.
Keywords: Dynamical Systems; Coupled Systems; Distributed Computing; Robot Swarms; Autonomous Mobile Robots; Gathering

Politisierung von Jugend – Zur Einführung in den Band - Dahmen, Stephan; Demir, Zeynep; Ertugul, Baris; Kloss, Daniela; Ritter, Bettina (Politisierung der Jugend)

Politisierung von Jugend

Empirische Zugänge zu organisational kontextualisierter Professionalität - Dahmen, Stephan; Henn, Sarah; Ritter, Bettina; Mohr, Simon (Sozialpädagogische Professionalisierung in der Krise?)

Hydrodynamic and Non-hydrodynamic Excitations in Kinetic Theory -- A Numerical Analysis in Scalar Field Theory - Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2308.04491)
Viscous hydrodynamics serves as a successful mesoscopic description of the Quark-Gluon Plasma produced in relativistic heavy-ion collisions. In order to investigate, how such an effective description emerges from the underlying microscopic dynamics we calculate the hydrodynamic and non-hydrodynamic modes of linear response in the sound channel from a first-principle calculation in kinetic theory. We do this with a new approach wherein we discretize the collision kernel to directly calculate eigenvalues and eigenmodes of the evolution operator. This allows us to study the Green's functions at any point in the complex frequency space. Our study focuses on scalar theory with quartic interaction and we find that the analytic structure of Green's functions in the complex plane is far more complicated than just poles or cuts which is a first step towards an equivalent study in QCD kinetic theory.

Wo lässt es sich im Universum leben? Eine Reise zu großen Sternen und kleinen Planeten - Hohmann, Sascha (Außerirdisches Leben)
Fast 5.000 Planeten in anderen Sternensystemen wurden inzwischen detektiert. Aber ist die Erde der einzige Planet, auf dem Leben möglich wäre? Kommt es dabei nur auf flüssiges Wasser und damit die Temperatur auf dem Planeten an oder gibt es noch andere Bedingungen, die Planet und Stern erfüllen müssen? Und warum sind die meisten bisher gefundenen Planeten dafür ziemlich ungeeignet? Diese und weitere Fragen sollen hier beantwortet werden.

Untersuchung des Einflusses von Relativverschiebungen während der Aushärtung auf die mechanischen Eigenschaften von Klebverbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Himmelskörper mit Geometrie - Hohmann, Sascha (Der Mathematikunterricht)

Experimentelle Untersuchung des Ermüdungsverhaltens von strukturellen Klebverbindungen und Berechnung der Lebensdauer unter Berücksichtigung der Spannungsanisotropie - Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien
Der vorliegende Band versammelt intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien und bietet so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien. Die Einzelbeiträge präsentieren kritische Reflexionen und Modifizierungen verschiedener Positionen der intersektionalen Forschung sowie Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene. Da wissenschaftliche und literarische ebenso wie zeitgenössische und historische Texte in verschiedenen Sprachen (Englisch, Deutsch, Italienisch, Niederländisch, Spanisch etc.) aufgegriffen werden, zeigt der Band auf, dass Machtstrukturen in unterschiedlichen kulturellen Kontexten Analogien aufweisen, deren Analyse von Differenzierungen verschiedener Herrschaftsstrukturen profitiert.
Keywords: Intersektionalität; Literaturwissenschaft; Literaturunterricht; Klassenlektüre; Auswahl; Textanalyse; Literatur; Erzähltheorie; Machtstruktur; Diskriminierung; Geschlechterrolle; Geschlechterverhältnis; Geschlechtsidentität; Rassismus; Soziale Klasse; Othering; Feminismus